The Influence of Customer Value, Product Innovation, and Brand Image on Customer Satisfaction at Black Cup Coffee Jalan Flamboyan Manado - Therok, Francisca Anggun; Mandey, Silvya L.; Wenas, Rudy S. (JR Education, 2023)
Black Cup is a local coffee shop that has five branches, one of which is on Jalan Flamboyan Manado. Data collection in this study used questionnaires and documentation with 50 respondents (saturated sample) who had made purchases more than twice using purposive sampling as the population. This research aims to analyze the influence of customer value, product innovation, and brand image on customer satisfaction at Kedai Kopi Black Cup Manado. The results of this research are: 1) Customer value has a significant influence on customer satisfaction at Kedai Kopi Black Cup Manado. 2) Product innovation has a positive and significant influence on customer satisfaction at the Black Cup Manado Coffee Shop. 3) Brand image has a positive and significant influence on customer satisfaction at the Black Cup Manado Coffee shop.